The FENDURA research project
FENDURA (The Female Endurance Athlete) is a research project led by the School of Sport Sciences at UiT The Arctic University of Norway, in close collaboration with NTNU, Olympiatoppen, Norges Skiforbund and Norges Skiskytterforbund. The projects aims at improving the sparse knowledge of how hormonal and other female-specific aspects impact exercise and performance among female endurance athletes. The project will examine female endurance athletes to better understand the impact of female-specific challenges.